Multisystem compensations and consequences in spastic quadriplegic cerebral palsy children - Wahyuni, Luh Karunia (Frontiers in Neurology, 2023)
Spastic quadriplegic cerebral palsy (CP) is a permanent neuromuscular disorder causing limitation on all four limbs following a lesion on the developing brain. Most children with spastic quadriplegic CP are identified to be Gross Motor Function Classification System (GMFCS) level V, thus they have more comorbidities compared to other types at lower levels. Spastic quadriplegic CP is characterized by weak and inactive postural muscles of the neck and trunk, hence, they will undergo a total body extension as a compensatory mechanism leading to an atypical movement pattern, that give rise to multisystem consequences that reduce their quality of life. The relationship between atypical movement patterns, compensatory strategies, and multisystem consequences have not yet been explored. In fact, these multisystem consequences aggravate their condition and make movement much more atypical, forming a vicious cycle. This review aimed to provide a summary and highlight the mechanism of atypical movement pattern, multisystem compensations, and consequences in spastic quadriplegic CP children. It is true that central nervous system (CNS) lesion in CP is non-progressive, however the multisystem consequences may impair overall function over time. An understanding of how compensatory strategy and multisystem consequences in spastic quadriplegic CP offers the opportunity to intervene as early as possible to improve their quality of life.